Distribusi dan Keanekaragaman Zooplankton di Waduk Jatibarang Kodya Semarang - Hariyati, Riche (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Jatibarang Reservoir is a dam built in Talun Kacang village, Kandri, Gunung Pati, Semarang t with the aim of Water Resources Management and flood control in Semarang City. The presence of Zooplankton in a waters has a close relationship with water quality and its interaction in the environment.The research aimed to find out the distribution and diversity of Zooplankton species in Jatibarang reservoir waters. The method used is Purposive Random Sampling method by dividing the sampling point into 4 research stations, namely Dermaga zone, middle zone, inlet zone, and outlet zone. From the result of this research, we get the type of zooplankton Brachionus sp., Cylops sp., Collotecha sp., Conochilus sp., Daphnia sp., Harringia sp., Rotaria sp., Keratella sp. and species from the Asphlanchnidae (Asphlanchinii) and Trichotriidae Family. The species diversity in Jatibarang reservoirs in each zone is low with abundance between 30-80 ind / L and the equalization and dominance of each low species. The dominant species is Brachionus sp. and Cyclops sp.Â Water quality measurement results show the waters of Jatibarang reservoir is good for the life of aquatic biotaÂ Keywords: Zooplankton, Jatibarang Reservoir, Diversity.